The relation between the anthropometric characteristics of fingers and cancer - Omid Mardanshahi; Jina Khayatzadeh; Soodabeh Shahidsales (Reviews in Clinical Medicine, 2017)
Anthropometry is a science of human body measurement that could be used for manufacturing artificial limbs or prosthesis, investigating body differences between populations, utilizing in forensics and criminology, or even in the diagnosis of some diseases. Two of the most important anthropometric characteristics are dermatoglyphic patterns and finger length. Many studies have evaluated the relation between these two characteristics in different diseases such as cancers. It assumed that dermatoglyphic patterns and finger length could be used as predictors of some cancers such as gastric, ovarian, prostate, testicular, and breast cancers. In this review, we evaluated the relation between dermatoglyphic variability and finger length in different cancers more precisely.